PTU-324 Pelvic radiation disease – when do patients present to gastroenterology services?. (22nd June 2015) - Stacey, R; Cox, B; Turner, J; Green, JT
Abstract : Introduction: Pelvic radiation disease (PRD) is a common condition causing gastrointestinal symptoms following radiotherapy treatment for pelvic cancer. Awareness of this patient group is increasing but there are few dedicated services in the UK at present. Patients can develop symptoms at varying times following radiotherapy. It is unclear at what point these patients tend to present to gastroenterology services. We aimed to assess the time from radiotherapy to presentation at a regional, non sub-specialised centre. Method: As part of a service evaluation a database search and retrospective note analysis was used to identify 109 patients who had been reviewed by our service between 2005 and 2014. Patients were seen in clinic and direct access endoscopy services. Patients were excluded from the analysis if they did not have both a clear date of radiotherapy commencement plus a clear date of initial review by the gastroenterology service. We analysed the time from radiotherapy to review by gastroenterology in these patients. Results: 67 patients were identified (36 women, 31 men). Time to event analysis was performed. 76% were initially seen in gastroenterology clinic and 24% were seen in direct access endoscopy. The median time to presentation was 2 years (95% CI 1.622 to 2.378). The Kaplan-Meier curve is shown in Figure 1 . The range was 0 to 26 years. 36% (n = 24) had radiotherapy for gynaecological cancer, 37% (n = 25) for urological cancer, 24% (n = 16) for colorectal malignancies and 3% (n = 2) for secondary malignancies (non pelvic primary). There was no significant difference in time to presentation between different types of malignancy (p = 0.713). 80% of patients presented in the first 5 years following radiotherapy. Conclusion: PRD usually presents within the first five years following radiotherapy, but our analysis clearly shows that delayed presentation is possible (up to 26 years in our evaluation). This time difference may lead both patients and physicians to neglect the impact the consequential effect of radiotherapy damage to the bowel can have, even several decades. As such gastroenterologists should be mindful of PRD in any patient who has previously had pelvic radiotherapy, even if it is in the distant past. Disclosure of interest: None Declared.